EFFICACY OF CONSUMING DATES (PHOENIX DACTYLIFERA) IN OVERCOMING GESTATIONAL FATIGUE AND ANEMIA IN SECOND TRIMESTER PREGNANT WOMEN: LITERATURE REVIEW - Muliatul Jannah; Rifana Azizatul Khairani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Pregnancy fatigue and anemia are common conditions in pregnant women in the second trimester and can increase the risk of maternal and fetal complications. Dates (Phoenix dactylifera) contain iron, folic acid, vitamin B complex, and natural sugars that have the potential to increase hemoglobin levels and energy metabolism. This study aims to analyze the efficacy of date consumption in overcoming gestational fatigue and anemia in pregnant women in the second trimester. The study used a literature review method by examining scientific articles from 2020–2025 obtained from the PubMed and Google Scholar databases. The study population consisted of articles related to date consumption, gestational fatigue, anemia, and pregnant women, with a sample of 12 articles consisting of 6 national journals and 6 international journals. The research instrument used a literature review sheet and data analysis was carried out descriptively through synthesis of research results. The results showed that consuming 6–7 dates (70–100 grams) per day for at least 14 days can increase hemoglobin levels by 0.965–2.3 g/dL and improve labor parameters related to reduced fatigue. The combination of dates and iron supplements has been shown to be more effective than iron supplements alone. In conclusion, dates are an effective and safe non-pharmacological intervention to help treat anemia and fatigue in pregnant women.